1989
DOI: 10.1099/00222615-29-4-243
|View full text |Cite
|
Sign up to set email alerts
|

Serum and tissue positivity for hepatitis B virus markers in histopathologically proven glomerulonephropathies

Abstract: Summary.To assess the pathogenic significance of hepatitis B virus (HBV) in glomerulonephritis (GN), 98 patients with histopathologically proven glomerulonephropathies were screened for HBV markers, complement components and levels of circulating immune complexes (CICs); and renal biopsies from 31 of them were examined for the presence of hepatitis B surface antigen (HBsAg), and its location, by immunoperoxidase staining. The HBsAg positive rate in the patients (who came from a population with 10% HBsAg positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…172 More recently, several in vitro and in vivo studies have further confirmed and extended such results by demonstrating that most plants of the genus Phyllanthus are able to inhibit the replication of HBV virus as well as the reverse transcriptase and DNA-polymerase. 11,[172][173][174][175][176][177][178][179][180][181][182][183] Very recently, Lee et al 182 reported that P. amarus extract prevented HBV infection by inhibiting the polymerase activity, decreasing episomal hepatitis B virus DNA content and suppressing virus release into the culture medium. Taken together, such findings are consistent with the notion that P. amarus extract has a beneficial effect against the hepatitis B virus, possibly through inhibition of polymerase activity, mRNA transcription, and replication.…”
Section: A Animal Studiesmentioning
confidence: 99%
“…172 More recently, several in vitro and in vivo studies have further confirmed and extended such results by demonstrating that most plants of the genus Phyllanthus are able to inhibit the replication of HBV virus as well as the reverse transcriptase and DNA-polymerase. 11,[172][173][174][175][176][177][178][179][180][181][182][183] Very recently, Lee et al 182 reported that P. amarus extract prevented HBV infection by inhibiting the polymerase activity, decreasing episomal hepatitis B virus DNA content and suppressing virus release into the culture medium. Taken together, such findings are consistent with the notion that P. amarus extract has a beneficial effect against the hepatitis B virus, possibly through inhibition of polymerase activity, mRNA transcription, and replication.…”
Section: A Animal Studiesmentioning
confidence: 99%